A community for students.
Here's the question you clicked on:
 0 viewing
anonymous
 one year ago
How do I find Y for ax+by+c=0
anonymous
 one year ago
How do I find Y for ax+by+c=0

This Question is Open

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0By Y you mean y right?

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0Then, to express y in terms of everything else, we have to isolate it on one side of the equal sign while having everything else on the other side of the equal sign. To do this, we use the algebraic operations of adding, subtracting, and dividing to solve for y. It can start like this.\[ax+by+c = 0 \implies ax + by + c +(c) = c\].

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0Since\[c + (c) = 0 \implies ax + by = c\]

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0Now, we can do the same thing for ax.\[(ax)+ax + by = (ax)  c \ \implies by = ax c\]

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0Now provided that \[b \neq 0 \], then \[\frac{ by }{ b } = \frac{ ax c }{ b } \ \implies y = \frac{ ax }{ b }  \frac{ c }{ b }\]
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.